Faktor-Faktor yang Berpengaruh pada Ketepatan Waktu Internet Financial Reporting - Darmayoni, Desak Made; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi, 2020)
The development of technology information influences the company to do financial reporting through the website, to make easier to spread the required potentials information and investment opportunities. This research aims to provide empirical evidence influence of leverage, liquidity, profitability, listing age, and auditor reputation on probability timeliness of Internet Financial Reporting. The research was conducted on Mining Sector Companies listed in the Indonesian Stock Exchange in 2014 – 2017. The samples were 128 companies with the purposive sampling method. For collecting data used observation and literature. The analysis technique used is a multivariate analysis by using binary logistic regression. Based on the results of the analysis was found that only profitability has a positive and significant effect on the probability of timeliness of Internet Financial Reporting. While leverage, liquidity, listing age, and auditor reputation have no effect on the probability of timeliness of Internet Financial Reporting.  Keywords: Internet Financial Reporting; Leverage; Liquidity; Profitability; Listing Age; Auditor Reputation.